Predictors of Major Adverse Cardiovascular Events in Stable Patients After ST Elevation Myocardial Infarction - Lidija Savic; Damjan Simic; Ratko Lasica; Gordana Krljanac; Sanja Stankovic; Igor Mrdovic; Milika Asanin (Clinics and Practice)
Background/aim: The aim of this study was to determine predictors of major adverse cardiovascular events, including MACE (mortality, non-fatal recurrent infarction, non-fatal stroke, and target vessel revascularization-TVR) in stable post-STEMI patients. Method: We analyzed STEMI patients without cardiogenic shock at admission included in our STEMI Register. The patients were treated with primary PCI. The follow-up period was eight years. Results: From 1 December 2006 to 31 December 2016, a total of 3079 patients were included in the Register. In the first year, MACE was registered in 348 (11.3%) patients. The remaining patients were considered stable. They were included in further analysis. At eight years, the rates were as follows: MACE 3.9%, non-fatal recurrent infarction 2.1%, TVR 1.8%, non-fatal stroke 0.5%, and mortality 2.1%. Predictors for 8-year MACE were age >60 years (60–69 vs. <60 years HR 1.65; 70–79 vs. <60 years HR 1.82; ≥80 vs. <60 years HR 3.16), EF < 50% (EF 40–49% HR 2.38; EF < 40% HR 2.32), diabetes mellitus (HR 1.49), and 3-vessel coronary artery disease (HR 1.44). Conclusions: Four predictors identified stable post-STEMI patients who remained at a higher risk for the occurrence of MACE. Stable post-STEMI patients with one or more of these risk factors may require more aggressive secondary prevention measures or a personalized approach to improve their prognosis.